Databases in computer science & their applications [ - Downing, Sona (New York : Learning Press, 2014)
This book deals with concepts of Databases in Computer Science & their Applications
1. Relational database -- 2. Data mining -- 3. Unique key and foreign key -- 4. Stored procedure and index (database) -- 5. Relational algebra -- 6. Database normalization -- 7. Cluster analysis -- 8. Association rule learning -- 9. Data dredging and data fusion -- 10. Biclustering and clustering high-dimensional data -- 11. Consensus clustering and decision tree learning
Keywords: Databases